Deformation analysis in advanced chronic kidney disease: an important prognostic indicator. (3rd October 2022) - Tsartsalis, D; Kakiouzi, V; Aggeli, C; Dimitroglou, Y; Latsios, G; Tsiamis, E; Giannou, P; Karampela, M; Petras, D; Vlachopoulos, C; Tousoulis, D; Tsioufis, C
Abstract: Background: Chronic kidney disease (CKD) is associated with a higher incidence of cardiovascular manifestations, particularly in patients with advanced renal impairment on long-term dialysis. Cardiac deformation analysis, assessed by speckle tracking echocardiography has been shown to be a significant prognostic index in various specific populations. Objective: To assess the prognostic value of deformation analysis measurements including both systolic parameters as left ventricular (LV) global longitudinal strain, and diastolic indices as left atrial (LA) strain, in patients with end-stage renal disease. Methods: We enrolled 67 patients (mean age 62.3±11.8, 65.7% men) with end-stage renal disease. Patients with a confirmed diagnosis of pre/existing cardiac conditions, such as obstructive coronary artery disease, heart failure, severe arrhythmias or severe valvular disease were excluded from the study. A comprehensive transthoracic echocardiography study was performed at baseline. All images were stored digitally and subsequent analysis was performed offline. LV global longitudinal strain (GLS) and LA strain were calculated semi-automatically using dedicated software. The primary endpoints of the study were major adverse cardiovascular events such as all-cause mortality, cardiovascular mortality, myocardial infarction, and hospitalizations for cardiac adverse events. The median follow-up was five years. Results: The study population had normal or mildly impaired systolic function with a mean LV ejection fraction (EF) of 49.17% (±10.41) while 70% of patients had reduced LV GLS, mean 14.35% (±4.49). Regarding LA parameters, 50% of our cohort had impaired LA strain: mean LA reservoir, LA conduit, and LA contractile reserve were 24.11% (±12.61), 10.56% (±5.88), and 13.60% (±9.15) respectively. The 5-year cumulative event-free survival was 58.2% (±6.7), while 30% of major events occurred in the first 2 years after baseline. Age had a moderate correlation with poor prognosis (p=0.013). Of the echocardiographic parameters LV EF, LV GLS, the conduit phase of LA strain, LA volume and various doppler parameters related to diastolic function, such as mitral E/A ratio and late mitral diastolic velocity A, were found to have a significant negative association with total prognosis (p=0.003, p=0.02, p=0.048, p=0.045, p=0.008, and p=0.017 respectively). Logistic regression analysis showed that of the different echocardiographic parameters LV EF, LV GLS, and the conduit phase of LA strain were significantly associated with the overall prognosis (p=0.009, p=0.007, p=0.05). The conduit element of LA strain was the strongest predictor among them (OR=0.77 p=0.04). Conclusion: Left ventricular systolic and diastolic dysfunction is a significant prognostic indicator in patients with end stage renal disease. Assessing cardiac mechanics with speckle tracking echocardiography could provide valuable information in this specific population. Funding Acknowledgement: Type of funding sources: None.